14.4k views
2 votes
Any help with this would be great, I'm not the best at these, and I'm behind from being sick and need to catch up.

Any help with this would be great, I'm not the best at these, and I'm behind from-example-1
User Katulus
by
5.4k points

1 Answer

3 votes

Answer:

Explanation:

Let say the following:

p = number of points

We know that they scored the same number of points in Game 1 and Game 2.

But in Game 3, they scored 6 points less than Game 1 and Game 2.

Therefore,

Game 1 = p

Game 2 = p

Game 3 = p - 6

To find the average you use the following formula:

Number of points / number of games = average

Basically,

(Game 1 + Game 2 + Game 3 ) / 3 = 63

So substitute the equations we made earlier and you get:


(Game 1 + Game 2 + Game 3)/(3) = 63\\(p + p + (p - 6))/(3) = 63

After this you just want to solve for "p"

Multiply both sides by 3 to get rid of the fraction:

p + p + (p - 6) = 63 x 3 = 189

3p - 6 = 189

Add 6 to both sides.

3p = 189 + 6 = 195

Divide both sides by 3

p = 195/3 = 65

So now we know p = 65 points. Substitute this back into our equations for each game:

Game 1 = p , Game 1 = 65 points

Game 2 = p , Game 2 = 65 points

Game 3 = p - 6 , Game 3 = 65 - 6 = 59 points

User Lorayne
by
5.0k points